"Modeling the Performance of the Reverse Osmosis System (RO) for Desalination using MATLAB Software." - عبد المنعم, شهد; عمار دباليز; رائد جعفر (Latakia University Journal -Engineering Sciences Series, 2024)
Reverse osmosis systems are considered systems in the water purification process that serve in various fields. Experimental models are an expensive and time-consuming approach to studying reverse osmosis membrane systems while the using of software-based computer models as an alternative method for predicting membrane performance, in order to predict future total decadent material values, a model of ANN industrial neural networks was created using MATLAB software, The samples were physically and chemically picked and analyzed for the plant's raw water and water in case of study, water treatment plant at Hamishu Metal Company , parameters affecting the value of the total decadent substances out (temperature, pH, pressure, total decadent substances) were measured for the water entering and exiting the station and then, a model of Neural Net Fitting-type of artifical neural networks was created, the results demonstrated the model's ability to predict R = 0.97 efficiency by comparison between calculated and measured values.